387 Effect of trace minerals (25-hydroxycholecalciferol, Zinc and Manganese) supplementation on the immune responses of livestock - Selvaraj, Ramesh K (J Anim Sci, 2020)
Micronutrients such as 25-hydroxycholecalciferol, zinc and manganese are included in livestock feed to achieve optimal growth and improved immune function. Vitamin D (cholecalciferol) modulates immune responses. The effect of Vitamin D on immune cells depends on the subtype of immune cells. Monocytes and macrophages constitutively express Vitamin D receptor and hence 1, 25-dihydroxycholecalciferol increases maturation and the microbicidal activity of macrophages by increasing the production of nitric oxide, antimicrobial proteins and inflammatory cytokines and eventually acts to stimulate the innate immune system. On the other hand, 1,25-dihydroxycholecalciferol suppresses the action of adaptive immune responses by inducing T regulatory cells and increasing the production of IL-10. Superoxide dismutases (SOD) catalyzes conversion of superoxide radicals to oxygen and hydrogen peroxide and is considered a major antioxidant defense system in livestock. SOD is a metalloenzyme with zinc, copper, and manganese as a cofactor. Though trace minerals have traditionally been supplemented in animal diets as inorganic salts such as zinc sulfate and manganese sulfate, other forms of trace minerals have recently been promoted owing to better stability, bioavailability and absorption. Feeding layer diets marginally deficient in zinc and manganese as sulfates decreased the SOD activity, spleen, IL-1 and cathelicidin relative mRNA levels and supplementing zinc and manganese as hydroxychloride (OHCl) reversed the decrease in SOD activity, spleen IL-1 and cathelicidin relative mRNA levels. Feeding broiler diets low in zinc and manganese as sulfates decreased SOD activity, while supplementing the feed with ZnOHCl reversed the decrease in SOD. Increasing the MnOHCl in birds fed higher amounts of ZnOHCl further increased the SOD activity suggesting synergistic effects between ZnOHCl and MnOHCl on SOD activity and IL-1 production. In conclusion, micronutrients act to modify the immune response in livestock, and the form of micronutrients fed can increase the bioavailability of the micronutrients to improve the immune response.